Experimental and numerical analysis of complex welded tubular DKYY-joints - Chiew, Sing Ping (2013)
The design of multi-planar welded tubular joints is still not fully developed and very often it is not covered in design codes due to the complexity of such structures. The joint position for multi-planar tubular structures is especially critical because there are many brace members which are welded onto the chord surface. Thus, many external forces which are transferred from the braces are applied directly to the chord. Among the various multi-planar tubular joint configurations, the DKYY-joint configuration is often used in tubular space structures to form long-span roofs. However, its design, failure modes and calculations of its joint capacity are not provided in any design code. As a result, it is necessary to carry out experimental investigation and finite element numerical analysis to understand further the behavior and failure process of this type of joint. This paper details an actual practical application where a full-scale specimen is investigated experimentally in a test programme. To improve its joint capacity, reinforcements such as strengthening plates are placed inside the brace members. The chord at the joint connection is thickened to avoid local buckling. The stresses at some critical positions on the braces and on the chord are measured from strain gauges and strain rosettes to monitor the failure process and the ultimate joint capacity is determined from experimental load-displacement relationship. Experimental results show that local buckling on the chord surface at the joint is avoided effectively due to the reinforcement to the chord by increasing the chord thickness locally and placing inner circular plate inside the chord. As the stiffness of the chord at the joint is improved efficiently, failure position moves to the brace, and thus the chord is protected. Finally, finite element analysis is conducted and the numerical results are compared against those obtained from experimental measurements.